2011
DOI: 10.1016/j.ijid.2011.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Varicella rates among unvaccinated and one-dose vaccinated healthy children in Izmir, Turkey

Abstract: Breakthrough varicella is not rare in Turkey where varicella infections are common. A longer interval since vaccination may be a risk factor for developing breakthrough varicella. Children who had been vaccinated >5 years previously were at risk for breakthrough disease. A two-dose varicella vaccine policy may be needed to provide improved protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…In Turkey, Kurugol et al [24] showed that among vaccinated children, 27.7% had breakthrough varicella and about 25% of breakthrough cases produced moderate or severe disease. Mortality from varicella is not common, but it occurs disproportionately among adolescents and adults due to pneumonitis and encephalitis [11].…”
Section: Incidence Of Varicella Related Hospitalization (Per 100000mentioning
confidence: 99%
“…In Turkey, Kurugol et al [24] showed that among vaccinated children, 27.7% had breakthrough varicella and about 25% of breakthrough cases produced moderate or severe disease. Mortality from varicella is not common, but it occurs disproportionately among adolescents and adults due to pneumonitis and encephalitis [11].…”
Section: Incidence Of Varicella Related Hospitalization (Per 100000mentioning
confidence: 99%
“…In non-outbreak situation studies, the breakthrough infection rate varies widely, ranging from 2.1% to 9.5% [6,7]. In Turkey, Kurugol et al [8] showed that 27.7% of children developed breakthrough infection from a total of 1683 vaccinated children and 24.7% of those had a moderate to severe disease course. In Taiwan, between 2000 and 2007, of more than 1 million children who received single-dose varicella vaccine, 2% had breakthrough infections and 0.016% required hospitalization and the overall vaccine effectiveness against varicella-related hospitalization was 85.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to explain the outbreaks. An increased risk for breakthrough disease has been noted with decreasing age at vaccination, time elapsed since vaccination, history of asthma, corticosteroid use, vaccination with varicella vaccine within 30 days of live attenuated measles-mumps and varicella vaccine [8]. While these associations have not been consistently reproduced in all studies, primary vaccine failure is evidently common in healthy young children after a single dose of live attenuated varicella vaccine and the most plausible explanation is that some immunized children do not develop humoral immunity to the varicella virus [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations